Glutathione regulates the transfer of iron-sulfur cluster from monothiol and dithiol glutaredoxins to apo ferredoxin - Wang, Lei (Protein Cell, 2012)
Holo glutaredoxin (Grx) is a homo-dimer that bridges a [2Fe-2S] cluster with two glutathione (GSH) ligands. In this study, both monothiol and dithiol holo Grxs are found capable of transferring their iron-sulfur (FeS) cluster to an apo ferredoxin (Fdx) through direct interaction, regardless of FeS cluster stability in holo Grxs. The ligand GSH molecules in holo Grxs are unstable and can be exchanged with free GSH, which inhibits the FeS cluster transfer from holo Grxs to apo Fdx. This phenomenon suggests a novel role of GSH in FeS cluster trafficking. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13238-012-2051-4 contains supplementary material, which is available to authorized users.